2024
DOI: 10.1182/bloodadvances.2023011632
|View full text |Cite
|
Sign up to set email alerts
|

Stromal alterations in patients with monoclonal gammopathy of undetermined significance, smoldering myeloma, and multiple myeloma

Lucienne Bogun,
Annemarie Koch,
Bo Scherer
et al.

Abstract: The hallmark of multiple myeloma (MM) is a clonal plasma cell infiltration in the bone marrow accompanied by myelosuppression and osteolysis. Premalignant stages like monoclonal gammopathy of undetermined significance (MGUS) and asymptomatic stages like smoldering myeloma (SMM) can progress to multiple myeloma (MM). Mesenchymal stromal cells (MSC) are an integral component of the bone marrow microenvironment and play an important role for osteoblast differentiation and hematopoietic support. While stromal alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous data from our group and others have indicated that conditioned media from AML cell lines could induce various alterations in MSCs related to growth and differentiation [ 4 , 20 ]. Building upon the hypothesis that soluble factors contribute to stromal alterations, we exposed healthy MSCs to conditioned Media (CM) derived from MNCs of healthy controls and patients with MDS, AML, ALL, and NHL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data from our group and others have indicated that conditioned media from AML cell lines could induce various alterations in MSCs related to growth and differentiation [ 4 , 20 ]. Building upon the hypothesis that soluble factors contribute to stromal alterations, we exposed healthy MSCs to conditioned Media (CM) derived from MNCs of healthy controls and patients with MDS, AML, ALL, and NHL.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs were cultured as previously described [ 20 ]. MNC fractions were cultured in RPMI + 20% FBS (Sigma Aldrich, St. Louis, MO, USA) and supplemented with IL-3, IL-6, SCF (all 10 ng/mL), and FLT-3Ligand (20 ng/mL), all from Peprotech, Hamburg, Germany, as previously described [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Blood Advances , in the article entitled “Stromal alterations in patients with monoclonal gammopathy of undetermined significance (MGUS), smoldering myeloma and multiple myeloma (MM),” Bogun et al 1 performed functional and molecular analyses on bone marrow-derived mesenchymal stem cells (MSCs) isolated from healthy individuals and patients with plasma cell neoplasms at various stages of disease, including MGUS, smoldering multiple myeloma (SMM), and MM. They found that MGUS MSCs already had a high proportion of senescent cells and reduced capacity for osteogenic differentiation and hematopoietic support, which became more pronounced with disease progression.…”
mentioning
confidence: 99%